Learning and loving of nature in the Anthropocene: How to broaden science with curiosity and passion - Bostad, Inga; Hessen, Dag O. (Studier i Pædagogisk Filosofi, 2019)
What does “belonging to nature” mean today and how can children and young people be inspired to experience this? What basic dilemmas and challenges arise between the requirement for critical thinking on the one side, and the experience of belonging and coexisting in nature on the other? In this article we will scrutinize the ideal of rational arguments and norms as stated in current policy documents and discuss how this best can promote curiosity and wonder, as well as a sense of relatedness and responsibility with nature that can inspire normative actions, We claim that critical thinking informed by a value-based ecology is needed to reveal the hidden curriculum of sustainable education; that is, a loss of “holistic” view in the footsteps of scientific diversification, a lack of curiosity and training of critical thinking, and a “denial of nature” characterized by a missed opportunity to raise the urgent attention towards environmental risks, that today should be a main mission in natural science education .